Tailorable, Lightweight and Superelastic Liquid Metal Monoliths for Multifunctional Electromagnetic Interference Shielding - Xu, Yadong; Lin, Zhiqiang; Rajavel, Krishnamoorthy; Zhao, Tao; Zhu, Pengli; Hu, Yougen; Sun, Rong; Wong, Ching‑Ping (Nano-Micro Letters, 2021)
Liquid metal (LM) has become an emerging material paradigm in the electromagnetic interference shielding field owing to its excellent electrical conductivity. However, the processing of lightweight bulk LM composites with finite package without leakage is still a great challenge, due to high surface tension and pump-out issues of LM. Here, a novel confined thermal expansion strategy based on expandable microsphere (EM) is proposed to develop a new class of LM-based monoliths with 3D continuous conductive network. The EM/LM monolith (EM/LMm) presents outstanding performance of lightweight like metallic aerogel (0.104 g cm−1), high strength (3.43 MPa), super elasticity (90% strain), as well as excellent tailor ability and recyclability, rely on its unique gas-filled closed-cellular structure and refined LM network. Moreover, the assembled highly conducting EM/LMm exhibits a recorded shielding effectiveness (98.7 dB) over a broad frequency range of 8.2–40 GHz among reported LM-based composites at an ultra-low content of LM, and demonstrates excellent electromagnetic sealing capacity in practical electronics. The ternary EM/LM/Ni monoliths fabricated by the same approach could be promising universal design principles for multifunctional LM composites, and applicable in magnetic responsive actuator. Highlights: 1 A confined thermal expansion strategy to fabricate liquid metal (LM)-based monoliths with continuous LM network at ultra-low content. 2 The results show a strong integration advantage of LM-based monoliths in density, mechanical strength, electromagnetic interference shielding effectiveness, and near field shielding effectiveness, as well as multi-functions such as magnetic actuation.